2014
DOI: 10.1007/s10163-014-0321-3
|View full text |Cite
|
Sign up to set email alerts
|

Selection of management option for solid waste from olive oil industry using the analytical hierarchy process

Abstract: This paper considers the process of selecting a appropriate olive mill solid waste management option in Jordan. Six alternatives were found to be possible options for olive mill solid waste management. Those alternatives are: animal feed, energy recovery, extraction of useful materials, co-combustion, fertilizers, and disposal without treatment. Prioritization of these six alternatives was performed through the analytical hierarchy process. Management options were prioritized based on three criteria: environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…However, the extraction process produces potent pollutants to obtain the residual oil [5]. Ecofriendly ways to recycle pomace is to use it to produce biogas [4] as animal feed, insecticide, herbicide, and compost after thermal concentration [6]. Moreover, three-phase centrifugation and pressure systems produce significant liquid waste, which is called olive vegetation water (VW) or mill wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…However, the extraction process produces potent pollutants to obtain the residual oil [5]. Ecofriendly ways to recycle pomace is to use it to produce biogas [4] as animal feed, insecticide, herbicide, and compost after thermal concentration [6]. Moreover, three-phase centrifugation and pressure systems produce significant liquid waste, which is called olive vegetation water (VW) or mill wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Unless managed properly, agro-industrial waste may pose both environmental and health problems (Sharma et al 1997). For example, Abu Qdais and Alshraideh (2016) reported that there are 118 olive oil mills in Jordan producing annually about 35,561 tons of solid waste from the olive oil industry. Deterioration of natural water bodies due to olive oil mill wastes is a serious problem as reported by Azbar (2004) and Alburquerque et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…The PROMETHEE (Preference Ranking Organization METHod for Enrichment of Evaluations) is a MCDM method introduced by Brans and Vincke [20] and developed by Brans et al [21]. It is well adapted to problems where a finite number of alternatives are to be ranked according to several, sometimes conflicting criteria by using six different functions [22].…”
Section: The Promethee Methodsmentioning
confidence: 99%